Главная

Алгебра 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

ГДЗ учебник по алгебрее 7 класс Ю.Н. Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г.

Раздел:

Номер №687

Упростите выражение:
а)
$(3b - 2)(5 - 2b) + 6b^2$
;
б)
$(7y - 4)(2y + 3) - 13y$
;
в)
$x^3 - (x^2 - 3x)(x + 3)$
;
г)
$5b^3 + (a^2 + 5b)(ab - b^2)$
;
д) (a − b)(a + 2) − (a + b)(a − 2);
е) (x + y)(x − y) − (x − 1)(x − 2).

Решение а

$(3b - 2)(5 - 2b) + 6b^2 = (15b - 6b^2 - 10 + 4b) + 6b^2 = 19b - 6b^2 - 10 + 6b^2 = 19b - 10$

Решение б

$(7y - 4)(2y + 3) - 13y = (14y^2 + 21y - 8y - 12) - 13y = 14y^2 + 13y - 12 - 13y = 14y^2 - 12$

Решение в

$x^3 - (x^2 - 3x)(x + 3) = x^3 - (x^3 - 3x^2 + 3x^2 - 9x) = x^3 - (x^3 - 9x) = x^3 - x^3 + 9x = 9x$

Решение г

$5b^3 + (a^2 + 5b)(ab - b^2) = 5b^3 + (a^3b - a^2b^2 + 5ab^2 - 5b^3) = a^3b - a^2b^2 + 5ab^2$

Решение д

$(a - b)(a + 2) - (a + b)(a - 2) = (a^2 + 2a - ab - 2b) - (a^2 - 2a + ab - 2b) = a^2 + 2a - ab - 2b - a^2 + 2a - ab + 2b = 4a - 2ab$

Решение е

$(x + y)(x - y) - (x - 1)(x - 2) = (x^2 - xy + xy - y^2) - (x^2 - 2x - x + 2) = x^2 - xy + xy - y^2 - x^2 + 2x + x - 2 = -y^2 + 3x - 2$